The emergence of an european asylum policy / L’emergence d’une politique européenne d’asile - Sousa, Constança Urbano de (2015)
The book covers the proceedings of the second Congress of lawyers specializing in European immigration and asylum law, jointly organizes by Universidade Autónoma de Lisboa and the Odysseus Academic Network for Legal Studies on Immigration and Asylum in Europe, on 15 and 16 November 2002 in Lisbon.